2020
DOI: 10.32709/akusosbil.547279
|View full text |Cite
|
Sign up to set email alerts
|

Katılımcı İklim Algısı ile Örgütsel Muhalefet Arasındaki İlişkinin İncelenmesi

Abstract: Siyaset bilimi kapsamında gelişen muhalefet kavramı, son yıllarda yönetim ve işletme alanında çalışan araştırmacılar tarafından da ele alınan konulardan biri haline gelmiştir. Örgüt içerisinde çalışanlara yönelik olumsuz davranışlar, eşit olmayan yönetim uygulamaları, çatışma ortamı ve örgütsel bağlılık düzeyi çalışanların muhalif tutum ve davranışlar sergilemelerine neden olan faktörler arasındadır. Yöneticilerin eşit, şeffaf ve katılımcı bir iklim meydana getirdikleri örgütler eleştiriye ve muhalefete açık b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…Motivational effects differed between employees with a high level of satisfaction with organizational commitment and employees with low organizational commitment. It was found that there are significant relationships between organizational commitment, performance, and motivation (Baltacı et al, 2016). Considering that one of the most important factors of people's quality of life is to provide satisfaction in the field of work, it can be said that organizational commitment is a factor that positively supports the quality of life in a sense.…”
Section: Discussionmentioning
confidence: 99%
“…Motivational effects differed between employees with a high level of satisfaction with organizational commitment and employees with low organizational commitment. It was found that there are significant relationships between organizational commitment, performance, and motivation (Baltacı et al, 2016). Considering that one of the most important factors of people's quality of life is to provide satisfaction in the field of work, it can be said that organizational commitment is a factor that positively supports the quality of life in a sense.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review conducted by the researcher, there is no study examining the relationship between job performance and organizational opposition. However, it has been found that it is associated with various variables such as organizational opposition and climate perception (Karalar, & Usta-Kara, 2020), personal values and psychological well-being (Acaray, 2018), five-factor personality model (Ökten, & Cenkçi, 2013), organizational power games (Korucuoğlu, & Şentürk, 2018) organizational cynicism and organizational commitment (Yıldız 2013) critical thinking dispositions (Püsküllüoğlu, & Altınkurt, 2018) and perception of professional self-efficacy (Bakan, et al 2017). The concept of organizational opposition has a very important place in the formation and development of democracy within the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Bu kapsamda öğretmenlerin bağlıkları ile sinizm ve muhalefet algıları arasında bir ilişkinin mevcut olduğu sonucu ortaya konulmaktadır (Yıldız, 2013). Karahan (2008) tarafından gerçekleştirilen "Hastanelerde Liderlik ve Örgütsel Bağlılık Arasındaki İlişkinin İncelenmesi" isimli çalışmada ise Afyonkarahisar Devlet Hastanesi'nde toplam 321 sağlık personeli üzerinde gerçekleştirilen anket uygulamasından elde edilen sonuçlara değinilmektedir. Bu kapsamda söz konusu çalışmada liderlik ile çalışanların bağlılıkları arasındaki ilişkilerin anlamlı olduğu, liderlik olgusunun sağlık çalışanlarının bağlılığına pozitif yönde etki yaptığı sonucuna ulaşıldığı ifade edilmektedir (Karahan, 2008).…”
Section: Normatif Bağlılıkunclassified